ECO-drainage towards sustainable urban environment - Nurfisah Binti Shamsuddin, Nurfisah (2010)
The project is to develop the drainage system to support an aquatic life that promotes balance ecosystems and at the same time examines the best infiltration devices based on the condition at the residential area in Bandar Seri Iskandar, Perak.